2022
DOI: 10.3390/robotics11020041
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective Review on Integrating VR/AR with Haptics into STEM Education for Multi-Sensory Learning

Abstract: As a result of several governments closing educational facilities in reaction to the COVID-19 pandemic in 2020, almost 80% of the world’s students were not in school for several weeks. Schools and universities are thus increasing their efforts to leverage educational resources and provide possibilities for remote learning. A variety of educational programs, platforms, and technologies are now accessible to support student learning; while these tools are important for society, they are primarily concerned with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 86 publications
2
19
0
Order By: Relevance
“…At the same time, AR users face the need to hold the smartphone, thus one hand is occupied and tactile interaction is limited 49 . Obviously, in the current research, the respondents still found it more convenient to cope with tasks using AR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, AR users face the need to hold the smartphone, thus one hand is occupied and tactile interaction is limited 49 . Obviously, in the current research, the respondents still found it more convenient to cope with tasks using AR.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, in the current research, the respondents still found it more convenient to cope with tasks using AR. However, performing more complex manipulations, as in the paper by Sanfilippo et al 49 , can be problematic in an AR environment.…”
Section: Discussionmentioning
confidence: 99%
“…For another instance, digital humans, the virtual human forms simulated by computers, could be the next‐decade's avatars as they are endowed with real humans' facial expressions, voices, and locomotions (Li et al, 2023) and could gain embodiment in the virtual world (Campbell & Jovanovic, 2022). Additionally, aligned with the development of multisensory technique solutions, multisensory XR, which can embody people through the replica of physical senses (Sanfilippo et al, 2022), could possibly replace nowadays' VR to be the dominant technological intermediary of virtual embodied experience.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, this same educational approach could be applied to new modules for the engineering mechatronics education curriculum. Moreover, the possibility of integrating virtual reality (VR)/augmented reality (AR) with haptics into these modules for multi-sensory learning may be considered [30,31].…”
Section: Discussionmentioning
confidence: 99%